Problems and Solutions of Vehicle Technical Condition Management (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The management of vehicle technical conditions is a critical aspect of modern transportation systems, impacting safety, efficiency, and environmental sustainability. This article explores the prevalent issues in vehicle technical condition management, including wear and tear, regulatory compliance, and the integration of advanced diagnostic technologies. It also discusses potential solutions, such as predictive maintenance, the use of telematics, and the implementation of stricter regulatory frameworks. By addressing these challenges, the article aims to provide a comprehensive overview of how effective management practices can enhance vehicle performance, reduce operational costs, and ensure regulatory compliance.